Financial performance and corporate values: Case in Jakarta Islamic Index - Lutfi Aulia Rahman; Razana Juhaida Johari; Abdulazeez Adewuyi Abdurraheem; Dwipraptono Agus Harjito (Asian Journal of Islamic Management (AJIM), 2021)
Purpose: This study aimed to determine the effect of financial performance on the company’s corporate value. The research is conducted by using companies listed in the Jakarta Islamic Index.Methodology: The sample in this study amounted to 14 companies, with the main criteria being companies that are consistently listed in the Jakarta Islamic Index during the study period. Data is obtained directly from the Indonesia Stock Exchange (BEI) and idx.com website. Quantitative analysis techniques used in this study include partial test, F test (simultaneous test), multiple linear regression analysis, and path analysis that previously conducted the classical assumption test, including normality test, autocorrelation, multicollinearity, and heteroscedasticity.Findings: The result of this research is that there is no influence of liquidity ratio to corporate value partially, there is a significant positive influence of profitability ratio to corporate value partially, there is a significant positive influence of solvency ratio to corporate value partially, there is a significant influence of liquidity ratio, profitability, and solvency to corporate value simultaneously. The variable of financial performance that has the most influence on corporate value is the profitability ratio.Originality: It is important to examine the stocks listed on the Jakarta Islamic Index because the majority of Indonesia's population is Muslim. Recently, many people have been aware of certain restrictions in Islam regarding what types of transactions are allowed and forbidden according to Islamic law.